Cuzco and Rome, Peruvians and Andalucians in Inca Garcilaso’s work - Del Pino Díaz, Fermín (2011)
In this paper I offer a socio-cultural explanation of Inca Garcilaso’s Romanist program, taking into account the analysis of his biographical anchorages in both Perú and Spain, specially his andalusian experience. To do so, I follow the social events he lived through (the recent conquest of the Islamic world and presence of Jewish converts), as well as the more cultural aspects of his stay in Spain (Royal and nobility classicism, relationship with the Jesuits). By broadening the scope of the interpretation of his texts, we are no longer talking merely about an individual and isolated (if aristocratic) experience, nor about a merely religious or literary option (even if it is expressed in such a way).